Dose ingested, vomiting, and outcome in patients ingesting a standard paraquat 20SL formulation. (2nd January 2023) - Deuster, Eileen; Tomenson, John A.; Mohamed, Fahim; Gawarammana, Indika; Buckley, Nicholas A.; Wilks, Martin F.; Eddleston, Michael
Abstract: Background: FAO specifications for liquid paraquat dichloride SL formulations require the use of an emetic agent to stimulate vomiting within 30 min of ingestion. To date, there is no high-quality evidence of efficacy, despite use of the PP796 emetic since 1979. We first examined the validity of patients' self-reported dose of paraquat ingested by examining the relationship with blood paraquat concentration and time to death for patients ingesting the standard paraquat SL formulation in a Sri Lankan cohort. As a secondary outcome, we assessed whether ingestion resulted in vomiting within 30 min and whether vomiting was associated with good outcome. Methods: Patients presenting with paraquat SL self-poisoning were prospectively studied in ten Sri Lankan hospitals in 2003–08. Data on reported dose ingested, incidence and timing of vomiting after ingestion, treatment received, plasma paraquat concentration, and outcome were collected prospectively on presentation to hospital. Time between ingestion and blood sampling was incorporated by covariate adjustment. Results: 441 patients were recruited to the case series, presenting a median (IQR) of 3.0 (1.5–8.1] h post ingestion. Outcome was known for 435 patients of whom 322 (74.0%) died within 42 days, a median of 1.3 (0.6–4.4) days post ingestion. Median reported dose ingested was 15 to <30 mL. There was a highly significant linear trend between log plasma paraquat and reported dose ingested ( p < .001); adjustment for the log of the time from ingestion to sampling further improved the model fit. Case fatality and median time to death also showed good agreement with estimated ingestion amount. 347/438 patients (79.2%) were stated to have vomited before reaching the study hospital with 300 (68.5%) vomiting within 30 min of ingestion; time to vomiting was unknown for a further 12 (2.7%). The proportion vomiting was strongly associated with reported dose ingested ( p < .001); of note the proportion vomiting within 30 min only increased to 83.3% for the highest ingestion group. Patients vomiting within 30 min had higher plasma paraquat concentrations ( p = .008), and higher hazard ratio in the adjusted Cox regression model of 2.01 (95% CI 1.45–2.77) compared to those who did not. Vomiting within 30 min was associated with a higher case fatality (241/295 [81.7%] vs 68/125 [54.4%], p < .001). Forty-three (47.3%) of the 91 patients who did not vomit before reaching hospital died (one had unknown outcome). Conclusion: Importantly, we found good agreement between reported dose ingested and plasma paraquat concentration, case fatality, and time to death, suggesting that the reported dose is a valid marker for the dose ingested. Vomiting occurred within 30 min for 68.5% of patients, exceeding the characteristics for a purported effective emetic in the FAO specifications. However, vomiting within 30 min was associated with approximately double the risk of death compared to those who did not vomit, larger paraquat ingestions, and higher blood paraquat concentrations. In addition, death occurred in many patients who did not vomit, and the proportion vomiting within 30 min only reached 82.1% for the highest ingested dose group. Overall, we found no evidence of benefit resulting from incorporation of the emetic, suggesting that the current FAO specification is not effective at preventing deaths after ingestion of the paraquat SL formulation.